Fatty acid composition indicates two types of metabolic syndrome independent of clinical and laboratory parameters - Žák, A; Burda, M; Vecka, M; Zeman, M; Tvrzická, E; Staňková, B (Physiological research, 2014)
Dietary composition and metabolism of fatty acids (FA) influence insulin resistance, atherogenic dyslipidemia and other components of the metabolic syndrome (MS). It is known that patients with MS exhibit a heterogeneous phenotype; however, the relationships of individual FA to MS components have not yet been consistently studied. We examined the plasma phosphatidylcholine FA composition of 166 individuals (68F/98M) with MS and of 188 (87F/101M) controls. Cluster analysis of FA divided the groups into two clusters. In cluster 1, there were 65.7 % of MS patients and 37.8 % of controls, cluster 2 contained 34.3 % of patients and 62.2 % of controls (P<0.001). Those with MS within cluster 1 (MS1) differed from individuals with MS in cluster 2 (MS2) by concentrations of glucose (P<0.05), NEFA (P<0.001), HOMA-IR (P<0.05), and levels of conjugated dienes in LDL (P<0.05). The FA composition in MS1 group differed from MS2 by higher contents of palmitoleic (+30 %), gamma-linolenic (+22 %), dihomo-gamma-linolenic (+9 %) acids and by a lower content of linoleic acid (-25 %) (all P<0.01). These FA patterns are supposed to be connected with the progression and/or impaired biochemical measures of MS (lipolysis, oxidative stress, dysglycidemia, and insulin resistance).
Keywords: stravovací zvyklosti; Male; Cluster Analysis; Phosphatidylcholines; mastné kyseliny; shluková analýza; Aged; mužské pohlaví; senioři; metabolický syndrom; Fatty Acids; Metabolic Syndrome; lidé; ženské pohlaví; Humans; fosfatidylcholiny; Female; lidé středního věku; Middle Aged; Feeding Behavior